2011
DOI: 10.1111/j.1476-5829.2011.00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety evaluation of combination vinblastine and toceranib phosphate (Palladia®) in dogs: a phase I dose‐finding study

Abstract: Combining drugs with known single-agent activity that lack overlapping dose-limiting toxicities and exert antitumor activity through different mechanisms could improve clinical outcome. As toceranib and vinblastine meet these requisites, a phase I trial was performed on the combination in dogs with mast cell tumors. The dose-limiting toxicity for the simultaneous combination was neutropenia and the maximally tolerated dose was vinblastine (1.6 mg/m2 every other week) concurrent with toceranib (3.25 mg/kg PO, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 38 publications
6
67
0
1
Order By: Relevance
“…Dogs were administered vinblastine every 2 weeks and toceranib on a Monday/Wednesday/Friday basis. The dose for vinblastine was 1.6 mg/m 2 given IV every 2 weeks based on a previously published study combining toceranib with vinblastine [37]. The starting dose for toceranib was 2.75 mg/kg with dose de-escalation down to 2.25 mg/kg permitted in the face of adverse events.…”
Section: Methodsmentioning
confidence: 99%
“…Dogs were administered vinblastine every 2 weeks and toceranib on a Monday/Wednesday/Friday basis. The dose for vinblastine was 1.6 mg/m 2 given IV every 2 weeks based on a previously published study combining toceranib with vinblastine [37]. The starting dose for toceranib was 2.75 mg/kg with dose de-escalation down to 2.25 mg/kg permitted in the face of adverse events.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, several studies have identified potentiation of the efficacy of paclitaxel, doxorubicin, and vincristine by the TKI imatinib in human preclinical models of KIT‐positive melanoma and Ewing's sarcoma, presumably owing to down‐regulation of important antiapoptotic pathways. A recent phase I study evaluating the safety of the combination vinblastine and TOC in dogs reported the necessity for substantial dose reductions of vinblastine in this combination therapy to prevent frequent and severe neutropenia . Together, these data suggest that combination therapies with TKIs may improve efficacy over single‐agent treatments alone.…”
mentioning
confidence: 99%
“…Clinically, it might be a challenge to find the optimum dose of small molecule drugs because patients exhibit a variation of tumour sensitivity to the drug relative to normal tissues. Toceranib phosphate (Palladia, SU11654) has been approved for the treatment of canine mast cell tumours, and it is beginning to be widely used to treat a variety of tumours in dogs . The current recommended dose of toceranib phosphate is 3.25 mg kg −1 , every other day (three times/week), and with this dosage, optimum plasma concentrations of 40 ng mL −1 were attained .…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used chemotherapy drugs for mast cell tumours are CCNU and vinblastine . Targeted therapy also has been attempted for canine mast cell tumours because this tumour expresses c‐kit and contains a mutated constitutively activated form . The c‐kit receptor is a one of a family of tyrosine kinase receptors that regulate cell signal transduction, cell survival, cell proliferation, and differentiation .…”
Section: Introductionmentioning
confidence: 99%